Health Promotion Model through Peer Group Education on Health Behavior Change - Lufthiani, Lufthiani; Zahara, Siti; Sitepu, Nunung Febriany (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Adolescence is also a period of mental change that can fluctuate. This pandemic results in changes in any behavior related to adolescents. The psychological condition of adolescents, who are generally still vulnerable and easily disturbed, is further exacerbated by conditions in the surrounding environment that do not support them in carrying out their usual activities. The purpose of the study was to determine the effect of the health promotion model through the peer group education method on changes in health behavior intentions in adolescents during the Covid-19 pandemic in Medan City. The research method used a quasi-experimental pretest and post-test design with one control group with a sample of 65 adolescents aged 13-18 years using purposive sampling technique. Data analysis was carried out using the Paired t test (p = 0.000). The results of the analysis stated that there was an effect of providing education using the peer group education method given to adolescents on changes in adolescent behavior during the covid 19 pandemic which was seen from the aspect of reproductive health, adolescent psychological disorders and the impact of using gadgets that must be supervised by parents